Existence and attractivity results for nonlinear first order random differential equations - Bapurao C. Dhage; Sotiris K. Ntouyas (Opuscula Mathematica, 2010)
In this paper, the existence and attractivity results are proved for nonlinear first order ordinary random differential equations. Two examples are provided to demonstrate the realization of the abstract developed theory.